2020
DOI: 10.1111/cjag.12259
|View full text |Cite
|
Sign up to set email alerts
|

Are multiple labels on food products beneficial or simply ignored?

Abstract: This study examines consumer preferences and willingness to pay (WTP) for organic wheat products exhibiting single labels, as well as multiple labels, including organic. The additional labels considered are related to the organic label (non-genetically modified organism [non-GMO]) or perceived as healthpromoting (gluten-free, low-carb, sugar-free). Study data were collected using a consumer survey conducted online in 2017 across 16 U.S. western states and analyzed using random parameter logit models. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
1
12
1
Order By: Relevance
“…Data from the first block of the bidding task showed the WTP was higher for sugar-free than for sugar-containing products, suggesting that the labels per se had an effect on participant's WTP. This supports the so-far debated hypothesis that sugar-free or reduced-sugar labeling increases individuals' WTP (16)(17)(18). Notably, in our design the label in question was presented with no additional nutrition claims in contrast to previous studies (16,18), limiting the possibility that the observed effect is confounded by information not related to sugar.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Data from the first block of the bidding task showed the WTP was higher for sugar-free than for sugar-containing products, suggesting that the labels per se had an effect on participant's WTP. This supports the so-far debated hypothesis that sugar-free or reduced-sugar labeling increases individuals' WTP (16)(17)(18). Notably, in our design the label in question was presented with no additional nutrition claims in contrast to previous studies (16,18), limiting the possibility that the observed effect is confounded by information not related to sugar.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, reduced-sugar labels have been associated with higher WTP, but also with lower perceived healthfulness and tastefulness (15,16). In contrast, Drugova et al (17) showed that people are willing to pay less for products labeled as sugar-free. On the other hand, some of the reduced-sugar labels that have been tested in the past, have revealed null effects (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Both are of interest because they are important predictors of purchasing intentions; they are reliable and, as such, brief and easy to adopt in a survey (Flynn and Goldsmith, 1999). These constructs were often used in consumer analyses, for example in describing patterns of organic vegetables consumption (Pieniak et al, 2010) or to estimate the willingness to pay for functional products (Drugova et al, 2020). These analyses found a relationship between these constructs and consumer behaviour, although subjective knowledge was considered a stronger predictor.…”
Section: Nutritional Awarenessmentioning
confidence: 99%
“…These constructs were often used in consumer analyses , for example in describing patterns of organic vegetables consumption (Pieniak et al. , 2010) or to estimate the willingness to pay for functional products (Drugova et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Baudry et al (2019) achieved results of associating higher organic food consumption with overall nutritional benefits (higher dietary scores) and lower body mass index (BMI). However, in a situation where the organic label is still associated with self-reported familiarity with organics than for tested knowledge (Drugova et al , 2020), information, raising awareness, promotion and the most important the organic food knowledge of consumers and emphasis on values that reflect their motivations are the crucial issues leading to the increased demand for this kind of food commodities (Demirtas, 2019; Tandon et al , 2020). Some studies brought even a deeper perspective of what health means to consumers, revealing purity (absence of food additives, preservatives and residues, or the naturalness of a food product), sensory pleasure (the experience of enjoyment while eating) and a holistic perspective on health (connection between the Earth and individuals as well as integration of different societal levels: micro, meso, macro) (Ditlevsen et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%